Psychological Well Being from the Perspective of Bhagavad Gita - Priyanka Joshi; Kamta Prasad Sahu (International Journal of Indian Psychȯlogy, 2022)
The essence of Bhagavad-Gita provides a psychotherapeutic model for mentally distressed patient in the form of a dialogue and discussion with Arjuna narrated by Lord Krishna. Six different aspects of wellness make up the psychological well-being, which can be improved by incorporating Bhagavad-Gita teachings. The insightful conversation depicted the state of Arjuna with clouded mind, dry mouth, sweating, burning sensation, shivering of limbs, fear and palpitations. Lord Krishna identified the signs of anxiety and offers the best course of action for controlling one’s emotions and desires with the help of intellectual equanimity, positive psychology, and other techniques. The paper is concluded in an attempt to provide an insight towards developing psychotherapeutic model for the modern society sufferers revealing the secrets of mental health as propounded by Lord Krishna in Shrimadbhagavad-Gita.